O início da docência e a trajetória profissional segundo a visão de professoras em final de carreira. - Pizzo, Silvia Vilhena (Universidade Federal de São Carlos, 2004)
The present work called The Beginning of Teaching Profession according to Ending Career Professors , has the aim to investigate the following inquiring question: What are the aspects that Elementary School first to fourth grade teachers at the end of their career remember from their initial professional course process of becoming a teacher? The theoretical reference used has involved studies about the construction of teacher career beginning, the professorship professional development, and learning by experience. The initial phase of the career is extremely important because it is the moment that the teaching bases are constructed. At this phase have occurred rare instants in teachers life becoming unique and transitory for them. It is a stage marked by the professor s attempts and mistakes, when the feelings of survival and discovery have appeared. The professional development of teachership involves personal growth dimensions, professionalism, and socialization. The teaching learning by experiences valorizes the practice in the classroom, and the experiences that are fundamental to the process of being teachers. In order to accomplish this research we counted with the participation of six educators that work in Public State Schools at least twenty-one years, that is considered the end of the career. The data were collected from semi-structured interviews made with teachers, and literally transcribed later. After these the statements were grouped for analysis according its similarities and discrepancies. The results obtained in this research indicate that: the beginning of the career is really, like shown in the literature, a difficult moment, with a lot of newness, conflicts, expectatives, rare episodes, and sometimes, the reality shock . The career maturity is related to the life experiences and personal route of each teacher, and the data have shown that the educators valorize the professional learning by experience as fundamental to the process of becoming professors. The reflection is seen like an important link between the acquired theories in the initial professional formation and the classroom practice.
Keywords: Professores formação; Aprendizagem profissional da docência; Professores iniciantes; Teaching learning; Educators formation; Beginner Professor; CIENCIAS HUMANAS::EDUCACAO